A review of insulin lispro for the treatment of patients with type 2 diabetes mellitus - Marina V. Shestakova; Svetlana V. Elizarova; Abdul Jabbar (Сахарный диабет)
A critical aspect of the treatment of most patients with type 2 diabetes mellitus (T2DM) is the initiation (and subsequent intensification) of insulin therapy when lifestyle interventions and oral anti-hyperglycaemic drugs fail to maintain or improve glycaemic control. There are several insulin treatment options available, including basal insulin, basal-bolus insulin and premixed insulin. Each of these options has advantages and disadvantages. The insulin lispro premixed insulin analogues, mix 25 (25% insulin lisproand 75% insulin lispro protamine suspension) and mix 50 (50% insulin lispro and 50% insulin lispro protamine suspension), which include intermediate- and rapid-acting components, were recently added to Russia’s national drug reimbursement program, increasing the treatment options for patients with T2DM. The aim of this review is to provide Russian physicians with current information on the efficacy and safety of insulin lispro, with a focus on insulin lispro mixtures, for the treatment of T2DM.